Studying the Role of Certain Levels of Blood Fats in Smokers - Hussein, Ruaa Saad; Mahmoud, Furqan Shaker; Mahdi, Nesreen Younes; Hussein, Malak Haider (Journal of Science in Medicine and Life, 2024)
One of the biggest risks to one's present and future health, smoking is currently spreading quickly throughout the developing globe and is thought to be the cause of 1.17 million deaths annually. Smoking poses a significant risk for cancer, peripheral vascular disease, stroke, and atherosclerosis. For the purpose of the study, samples were taken from 15 different students who were smokers and 15 students who were not smokers. The following laboratory tests were carried out: blood examinations Analysis of total cholesterol and triglycerides (HDL, LDL, T-CHO, TRIGLYCERIDES) was part of this. According to the study's findings, there was a minor variation in the percentage of all analyses that included T-CHO, HDL, and LDL. Smokers have a reduced proportion of it in their blood serum (0.4–10.1) compared to non-smokers, which poses health hazards.